The Human Right to Water in South Africa and the Mazibuko Decisions - Humby, Tracy; Grandbois, Maryse (Les Cahiers de droit, 2010)
The right of access to sufficient water in the South African Constitution has for long been regarded as progressive in a global context where the human right to water is still a subject of contention. In its recent decision handed down in the Mazibuko matter, the South African Constitutional Court interpreted the right of access to sufficient water for the first time and clarified the nature of the State’s obligations which flow from this right. It also commented upon the role of the courts in adjudicating the human right to water. This article describes the passage of the Mazibuko matter and the manner in which the lower courts interpreted the right of access to “sufficient water” as well as outlining the Constitutional Court’s decision in the context of access to water services provision in South Africa.